2015
DOI: 10.1016/j.tet.2014.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of diverse β-quaternary ketones via palladium-catalyzed asymmetric conjugate addition of arylboronic acids to cyclic enones

Abstract: The development and optimization of a palladium-catalyzed asymmetric conjugate addition of arylboronic acids to cyclic enone conjugate acceptors is described. These reactions employ air-stable and readily-available reagents in an operationally simple and robust transformation that yields β-quaternary ketones in high yields and enantioselectivities. Notably, the reaction itself is highly tolerant of atmospheric oxygen and moisture and therefore does not require the use of dry or deoxygenated solvents, specially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 64 publications
7
54
0
Order By: Relevance
“…14,19 While we noted that the addition of water had no deleterious effect in our initial report, we did not consider water as an important additive because we believed the stoichiometric arylboronic acid, and adventitious water therein, to be an adequate proton source to turn over the catalyst. However, attempts to perform the reaction on large scale failed to fully convert enone 1 to product ketone 4 , resulting in only a moderate yield.…”
Section: Further Reaction Developmentmentioning
confidence: 94%
“…14,19 While we noted that the addition of water had no deleterious effect in our initial report, we did not consider water as an important additive because we believed the stoichiometric arylboronic acid, and adventitious water therein, to be an adequate proton source to turn over the catalyst. However, attempts to perform the reaction on large scale failed to fully convert enone 1 to product ketone 4 , resulting in only a moderate yield.…”
Section: Further Reaction Developmentmentioning
confidence: 94%
“…Similar results were obtained with BINAM-based NHC ligands 56 and pre-formed palladacycles bearing chiral naphylphosphine ligands. 57 Chiral pyridinooxazoline (PyOX) (Scheme 21ii) 58 and bisoxazoline (BOX) 59 ligands were effectively used to construct chiral quaternary centres. Miyaura and co-workers found that addition of a silver salt greatly enhanced the enantioselectivity in linear substrates, presumably by accelerating the transmetalation step of the arylboronic acid onto palladium (Scheme 21iii).…”
Section: Examples Of Synthetically Enabling Protodepalladation Reactionsmentioning
confidence: 99%
“…General Information 1 H NMR spectra were recorded at 300 MHz or 500 MHz; 13 C NMR spectra were recorded at 75.5 MHz or 126 MHz with the solvent peak used as the internal reference (7.26 and 77.0 ppm for 1 H and 13 C respectively); 19 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 polarimeter. The enantiomeric excess (ee) of the products was determined by chiral stationary phase HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…In 2011, Stoltz and coworkers reported the addition of arylboronic acids to b-substituted cyclic enones catalyzed by Pd(TFA) 2 / Pyrox (IVa). [18] This system efficiently generates benzylic [19] and bis-benzylic [20] quaternary sterocenters. Minaard and co-workers expanded this scope to lactones and other acceptors using PdCl 2 /Box (IIIa) catalyst in combination with AgSbF 6 (20 mol%).…”
Section: Introductionmentioning
confidence: 99%